‘What is Ours and What is Not Ours?’: Inclusive Imaginings of Contextualized Mathematics Teacher Education - Luitel, Bal Chandra; Taylor, Peter (Springer, 2010)
How can we address the problem of culturally decontextualised mathematics education faced by Nepali students who, as citizens of the world’s most recent democracy, are far from realising the positive contribution of mathematics education to the development of a socially just, egalitarian and pluralist society?